Thailand Government Strategy and Policy in Handling The COVID-19 Pandemic - Tunggal, Hamas Nurhan Rabbani; Putra, Madda Asyafa; Salim, Mario Ben (Journal of ASEAN Dynamics and Beyond, 2020)
The Covid-19 pandemic destroyed various countries from various aspects. One of the countries affected is Thailand. For Thailand itself, they are more disadvantaged in the economic sector. Given that one of the leading economic suppliers in Thailand is from the tourism sector. The sector has also been devastated due to the absence of foreign tourists visiting Thailand due to the pandemic. With this, the local Government has taken various ways to restore the situation to normal. Four things are under the Government's spotlight, including the health insurance system, the application of social distancing, the imposition of national emergency status, and economic stimulus. With these several things, it can be said that this journal will discuss how the Thai government policy in fighting Covid-19 from the health sector, the economy, and others. In his efforts, many polemics occurred due to quite controversial policies. One example is when the Government asked rich people in Thailand to help solve the problem. It brought a lot of negative response on social media, for example, is much-scattered hashtag #BeggarGovernment.